2020
DOI: 10.1002/joa3.12442
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between red cell distribution width and cardiac autonomic function in heart failure

Abstract: Background Both increases in red cell distribution width (RDW) levels and autonomic dysfunction are considered to be correlated with worsening heart failure. However, the relation of RDW levels to autonomic function remains uncertain. We aimed to investigate the association of RDW levels in heart failure with autonomic function, evaluated by heart rate variability (HRV) and heart rate turbulence (HRT), and prognosis. Methods We studied 222 hospitalized patients with stable heart failure before discharge, and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…It seems hence rational that this simple parameter may reflect the adverse prognosis in many clinical conditions. There are several studies indicating the prognostic performance of advanced RDW level in coronary artery disease ( 11 , 12 ), heart failure ( 13 , 14 ), atrial fibrillation ( 15 , 16 ), and new-onset stroke ( 17 , 18 ). Existing reports on the relationship between RDW and CKD are comparatively sparse.…”
Section: Introductionmentioning
confidence: 99%
“…It seems hence rational that this simple parameter may reflect the adverse prognosis in many clinical conditions. There are several studies indicating the prognostic performance of advanced RDW level in coronary artery disease ( 11 , 12 ), heart failure ( 13 , 14 ), atrial fibrillation ( 15 , 16 ), and new-onset stroke ( 17 , 18 ). Existing reports on the relationship between RDW and CKD are comparatively sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more studies have shown that the RDW value can be useful in predicting the poor prognosis in patients with cardiovascular diseases including atrial brillation [15], heart failure [16], and cardiogenic shock, etc. [17].…”
Section: Discussionmentioning
confidence: 99%
“…12 In literature reviews, it is recommended to be cautious in terms of nutritional deficiencies, renal failure, stress, increased neurohormonal activity, cardiac events and heart failure in case of high RDW. [22][23][24] It is not certain that the above-mentioned problems are caused by high RDW alone, it suggests that high RDW may indicate important problems.…”
Section: Itemsmentioning
confidence: 99%